2022
DOI: 10.3233/mgc-210152
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of ZnO nanoparticles and comparison of 2,4-dinitrophenol removal efficiency using photocatalytic, sonocatalytic, and adsorption processes

Abstract: In the present work, the extract of a paper-flower species called Bougainvillea spectabilis was used to green synthesis of ZnO nanoparticles (NPs). The synthesized ZnO NPs was confirmed by XRD, SEM, TEM, EDS, and FTIR techniques. Then, the ability of ZnO NPs to remove 2,4-dinitrophenol from aqueous solutions was investigated using photocatalytic and sonocatalytic processes. All experiments were carried out in a batch system and the effects of pH, NPs dosage, concentration, and contact time were evaluated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In another work, Bougainvillea spectabilis flowers were used to create the extract for the synthesis of ZnO. 48 In this study, green ZnO nanoparticles could enhance the removal of 2,4-dinitrophenol at an equilibrium capacity of 42.6–70.4 mg g −1 . The authors demonstrated that the removal of 2,4-dinitrophenol by green ZnO nanoparticles was endothermic with an enthalpy (Δ H ) value of 7.38 kJ mol −1 .…”
Section: Applications Of Zno Nanoparticles Biosynthesized Using Flora...mentioning
confidence: 82%
See 1 more Smart Citation
“…In another work, Bougainvillea spectabilis flowers were used to create the extract for the synthesis of ZnO. 48 In this study, green ZnO nanoparticles could enhance the removal of 2,4-dinitrophenol at an equilibrium capacity of 42.6–70.4 mg g −1 . The authors demonstrated that the removal of 2,4-dinitrophenol by green ZnO nanoparticles was endothermic with an enthalpy (Δ H ) value of 7.38 kJ mol −1 .…”
Section: Applications Of Zno Nanoparticles Biosynthesized Using Flora...mentioning
confidence: 82%
“…In another work, Bougainvillea spectabilis owers were used to create the extract for the synthesis of ZnO. 48 In this study, green ZnO nanoparticles could enhance the removal of 2,4dinitrophenol at an equilibrium capacity of 42.6-70.4 mg g −1 .…”
Section: Adsorptionmentioning
confidence: 84%